2006
DOI: 10.1182/blood-2005-07-2854
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin inhibits in vitro erythroid colony formation at reduced erythropoietin concentrations

Abstract: The anemia of chronic disease (ACD) results from 3 major processes: slightly shortened red cell survival, impaired reticuloendothelial system iron mobilization, and impaired erythropoiesis. Hepcidin is an acute-phase protein with specific iron regulatory properties, which, along with the anemia seen with increased hepcidin expression, have led many to consider it the major mediator of ACD. However, if hepcidin is the major factor responsible for ACD, then it should also contribute to the impaired erythropoiesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 24 publications
6
83
0
1
Order By: Relevance
“…In this context, we observed a direct relationship between DMT1 and MTP1 in S2 segments under hemolytic crisis, concomitant with reduced Prohepcidin expression in this tubular segment. The regulatory relationship between hepcidin and iron transporters has been widely studied by other authors in several tissues (2,7,11). Interestingly, the changes in protein expression observed in renal segments were accompanied by an increase in iron deposits.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we observed a direct relationship between DMT1 and MTP1 in S2 segments under hemolytic crisis, concomitant with reduced Prohepcidin expression in this tubular segment. The regulatory relationship between hepcidin and iron transporters has been widely studied by other authors in several tissues (2,7,11). Interestingly, the changes in protein expression observed in renal segments were accompanied by an increase in iron deposits.…”
Section: Discussionmentioning
confidence: 99%
“…29 It has been speculated that baseline inefficiency of iron utilization due to increased uptake with simultaneous efflux through ferroportin may provide a buffer to protect the developing erythrocyte from iron deficiency in inflammation, where increased hepcidin blocks iron efflux from erythrocytes. However, hepcidin has been shown to negatively regulate the development of erythroid precursors in vitro, 30 raising the possibility of more complex effects.…”
Section: Erythroid Precursorsmentioning
confidence: 99%
“…Previous studies have shown that comparison between hepcidin and CRP may serve as a quick and easy method for identifying the difference between iron deficiencies, micro inflammation or mixed anaemia [18]. In addition to its effect on iron metabolism; hepcidin may contribute to rhEPO resistance through a direct inhibitory effect on erythroid progenitor proliferation and survival [5]. Other studies revealed contradictory results; Kato et al [19] found hepcidin levels were not different between rhEPO-responsive and rhEPO resistant dialysis patients, whereas Ford et al [20] found no relationship of hepcidin with rhEPO dose.…”
Section: Discussionmentioning
confidence: 99%
“…Hepcidin inhibits the efflux of iron into plasma transferrin by down regulating ferroportin, the efflux channel for iron in macrophages and in enterocytes [4]. Enhanced synthesis of hepcidin thus leads to inhibition of iron absorption in the small intestine and sequestering of iron in macrophages, resulting in limited iron availability for erythropoiesis [5]. Increased iron stores and inflammation induce hepcidin synthesis in the liver, whereas suppression occurs during hypoxia, iron deficiency, and increased erythropoiesis [6].…”
Section: Introductionmentioning
confidence: 99%